Habilidades investigativas y estrategias de búsqueda de información académica en tesistas de Enfermería - Correa-Sánchez, Yaneth Rosmery (2025)
Objective. To determine the relationship between research skills and academic information search strategies among nursing thesis students at Universidad de Huánuco, Peru. Methods. Quantitative, observational, correlational study. The population consisted of 313 thesis students, from which a sample of 173 students was selected through stratified probabilistic sampling. The Research Skills Scale and a questionnaire on academic information search strategies were applied, both of which had been previously validated and tested for reliability. For inferential analysis, Spearman’s correlation was used with a significance level of p < 0.05. Results. Regarding research skills, more than half of the participants were at a developed level, with the instrumental dimension standing out (72.3%), while overall, 52% were classified as developed. Concerning information search strategies, there was a predominance of efficient use of databases (60.1%) and truncation tools (54.3%), although limitations were observed in the use of Boolean operators. At the inferential level, a positive and significant correlation was identified between research skills and search strategies (rho = 0.634; p < 0.001), with the problematization dimension showing the highest correlation (rho = 0.728; p < 0.001). Conclusions. It was determined that research skills are significantly and positively related to academic information search strategies.